Profitability and Financial Feasibility Analysis of Hydroponic Vegetable Business at Bahagia Farm - Nur Aini; Abu Bakar; Ekalia Yusiana (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to explore the profitability and financial feasibility aspects of hydroponic farming. Methodology: The study was conducted at Bahagia Farm, located in Bahagia Village, Babelan District, Bekasi Regency, from May 2023 to June 2023. The Non-Probability Sampling technique with a Saturated Sample (census) approach was used for sample selection. Data collection involved primary information from interviews, direct observations, and original documents, analyzed through profitability and financial feasibility analysis. Results: The results indicate that the farming business is profitable and feasible, with profitability indicators such as a Gross Profit Margin of 75.21% and a Net Profit Margin of 48.83%. Findings: The financial analysis shows a Net Present Value (NPV) above the neutral point at Rp553,272,251, a Net B/C ratio of 2.63, an Internal Rate of Return (IRR) of 41.82%, and a payback period of 2 years, 4 months, and 18 days. Novelty: This research provides detailed insights into the financial viability and profitability of hydroponic farming, enhancing understanding of its economic potential. Originality: The study offers a comprehensive analysis of economic benefits and financial metrics, contributing to knowledge on sustainable agriculture practices. Conclusions: Hydroponic farming at Bahagia Farm is profitable and financially feasible, making it a viable agricultural practice. Type of Paper: Empirical Research Article